Метод адаптивного сглаживания электрохимических сигналов в хронопотенциометрии - Суровцев, И.В. (Управляющие системы и машины, 2015)
Рассмотрен метод адаптивного сглаживания с использованием точки экстремумов исходного сигнала и его производной для определения точек перегиба на интегральном сигнале. По найденным точкам интегральный сигнал интерполируется и дифференцируется в полезный сигнал, при этом изменяются только зашумленные участки электрохимического сигнала. Розглянуто метод адаптивного згладжування з використанням точки екстремумів вхідного сигналу та його похідної для визначення точок перегину на інтегральному сигналі. За знайденими точками інтегральний сигнал інтерполюється та диференціюється в корисний сигнал, при цьому змінюються тільки зашумлені ділянки електрохімічного сигналу. Introduction. In chronopotentiometry for the data processing systems it is important to apply the method of smoothing that does not distort the form of the intensity signal and does not increases the measurement error of the toxic elements concentration. Purpose. The purpose of research is to create a method of smoothing individual sections of the signal for which the interval between the points of extrema or the kinks less interval of filter. Methods. The intervals between the inflection points which correspond to the points of the original signal extrema are found on the calculated integral signal. If the interval is less than a predetermined value, the internal points are removed; the integral signal is interpolated and is differentiated back into a useful smoothed signal.